Architectural Guidelines for Building a Special Learning Environment for Children in Need. (13th May 2015) - Povian, Cristina-Maria; Dumitrescu, Cristian
Abstract: The study environments are the problem analysed from an educational point of view, but closely correlated to the architectural, psychological and social principles. This article starts from the idea that a learning environment adequate to the children's requirements represents the key to their better development and implicitly investing in our children's education we invest in our future as society. A challenge for the educational environment is the rehabilitation of the children living on the street. They are facing addictions, and they have developed a vicious behaviour, determined by their life on the street, they survive in unhealthy environments and they do not enjoy even the minimal hygiene conditions. Numerous studies in the field of resilience have proved that, the ambient environment and the learning environment have a determining role in this process. The purpose of this article is that to analyse educational programs dedicated to them from architectural, psychological, political, economic and social point of view, trying to identify the main positive and negative factors in the centres dedicated to them and stating a few architectural principles for a better development of their learning and rehabilitation environment.